Content marketing for dummies - Gunelius, Susan (Hoboken, NJ : Wiley Pub., 2011)
Learn what content marketing is and how to develop a strategy for your business. The trick to success lies in understanding both the tools available and the strategic thought process that makes them work.
Getting started with a content marketing plan -- Marketing with long-form content -- Marketing with short-form content -- Engaging in online conversations to share content -- Achieving long-term success -- The part of tens.
Includes index.
Keywords: Internet marketing; Online social networks